“El maltrato grave, reiterado por parte de los progenitores y su incidencia en la privación de la patria potestad en las resoluciones tramitadas en la Unidad judicial Mujer, Niñez y Adolescencia con sede en el cantón Riobamba durante el año 2015” - Malán Lema, María Virginia (2017)
the serious mistrear, reiterated by the progenitors and its incidence in the deprivation of the country potestad in the resolutions processed in the judicial unity women, children and adolescence with headquarters in cantón riobamba during the year 2015. ABSTRACT: In our country there is an extensive regulation regarding children and adolescents whose purpose is to protect the rights of each one of them and that guarantee their development. One of the fundamental rights is to have a family relationship and a paternal-filial relationship with their parents, but when parents act so carefree with their children to the point that they reach their aggression, causing them physical and Psychological, in these cases the State through laws that protect children intervene within the family as a guarantor of the fundamental right of children and adolescents. And for that reason, in many cases by judicial decision deprive them of the motherland protest to one or both parents as the case may be, this is established by the Organic Code of Children and Adolescents in its art. 113. Due to the gravity of the causes that deprive parental authority, the need to deprive parents of the exercise of parental authority over their children when they are put in danger or at risk is justified by a process Judicial process. It is important to emphasize that the Constitution of the Republic of Ecuador, ensures the best interests of the child and adolescent, but also for their physical and integral development.